2014
DOI: 10.1126/science.1256985
|View full text |Cite
|
Sign up to set email alerts
|

Growth of nitrite-oxidizing bacteria by aerobic hydrogen oxidation

Abstract: The bacterial oxidation of nitrite to nitrate is a key process of the biogeochemical nitrogen cycle. Nitrite-oxidizing bacteria are considered a highly specialized functional group, which depends on the supply of nitrite from other microorganisms and whose distribution strictly correlates with nitrification in the environment and in wastewater treatment plants. On the basis of genomics, physiological experiments, and single-cell analyses, we show that Nitrospira moscoviensis, which represents a widely distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 43 publications
7
170
0
1
Order By: Relevance
“…Hydrogenase-encoding genes were also identified in the genomes of multiple seemingly obligate methane oxidisers, ammonia oxidisers and nitrite oxidisers (Supplementary Table S1), suggesting H 2 may serve as a fuel source for growth or survival of these bacteria and archaea. In line with this, it was recently demonstrated that Nitrospira moscoviensis of the phylum Nitrospirae is capable of hydrogenotrophic growth using a group 2a [NiFe]-hydrogenase (Koch et al, 2014). Aerobic H 2 oxidation may therefore provide hitherto-unrecognised metabolic flexibility in microorganisms controlling the methane and nitrogen cycles.…”
Section: Discussionmentioning
confidence: 62%
“…Hydrogenase-encoding genes were also identified in the genomes of multiple seemingly obligate methane oxidisers, ammonia oxidisers and nitrite oxidisers (Supplementary Table S1), suggesting H 2 may serve as a fuel source for growth or survival of these bacteria and archaea. In line with this, it was recently demonstrated that Nitrospira moscoviensis of the phylum Nitrospirae is capable of hydrogenotrophic growth using a group 2a [NiFe]-hydrogenase (Koch et al, 2014). Aerobic H 2 oxidation may therefore provide hitherto-unrecognised metabolic flexibility in microorganisms controlling the methane and nitrogen cycles.…”
Section: Discussionmentioning
confidence: 62%
“…The ecophysiological flexibility, which results from the aerobic and anaerobic use of formate (this study) or H 2 (23,24), may enable Nitrospira to survive periods of nitrite or oxygen deprivation. These metabolisms uncouple the growth of NOB from the nitrification process and could contribute to the unexpected higher abundances of NOB compared with AOM observed in nitrifying activated sludge, biofilm, and freshwater sediment (10,20,47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrospira moscoviensis even grows by aerobic hydrogen oxidation as an alternative lifestyle outside the N cycle (23). Furthermore, this organism can reduce nitrate with H 2 as an electron donor, but under these conditions, growth was not detected (24).…”
Section: Significancementioning
confidence: 99%
“…Nitrospira represents the most widespread group of known NO 2 À -oxidizing bacteria found in many different aquatic and terrestrial environments, including Fe water-pipes, drinking water treatment systems, and wastewater treatment plants (Daims et al, 2001). However, knowledge on the ecophysiology of the mainly uncultured, slow-growing Nitrospira is limited and only two genome sequences have been obtained to date from ''Candidatus N. defluvii'' (Lücker et al, 2010) and a draft genome sequence of N. moscoviensis (Koch et al, 2014). Interestingly, the genome of ''Candidatus N. defluvii'' contains besides an arsC-type arsenate reductase, as functional component of a potential As resistant mechanism, also an aioA-like respiratory arsenite oxidase gene (Lücker et al, 2010).…”
Section: Diversity Distribution and Abundance Of Nitrifying Microorgmentioning
confidence: 99%
“…However, the growth of NO 2 À -oxidizing bacteria by aerobic arsenite oxidation has not been demonstrated. Recently, growth of N. moscoviensis with hydrogen as electron donor has been shown, suggesting a chemolithoautotrophic lifestyle of bacterial NO 2 À -oxidizers outside the nitrogen cycle (Koch et al, 2014). In the sand filter the abundance of Nitrospira sp.…”
Section: Diversity Distribution and Abundance Of Nitrifying Microorgmentioning
confidence: 99%